La defensa técnica de la Defensoría del Pueblo y la vigencia de los derechos constitucionales de los consumidores. - Tapia Salazar, Evelyn Mishel (2023)
In the daily life of people, different needs have always arisen, among them, that of acquiring products or services in order to satisfy an imminent need, so throughout history, market relations have always existed, and with it, a direct relationship between supplier and buyer, in ancient times, as the supplier, who had the most money, was the one who had the most power in the market, thus abusing the vulnerable part, who had less money, who was at the expense of what the provider offered, even in the face of total disinformation, trampling the rights of the consumer in such a way, after a long wait and seeing how their rights as consumers have been trampled and they have been forgotten the obligations of the suppliers, the fight against the protection of consumers begins to arise, within the commercial relationship, in such a way that the first manifestations regarding the creation of law towards the consumer, which took a long time. Currently, despite having a law, it is entirely unknown even by consumers, which is why they continue to be exposed to market threats. In Ecuador, we have a Constitutional Charter which recognizes the rights of consumers and users, as well as the Organic Law of the consumer, a specific law that deals with the protection of consumer rights as well as the obligations that providers have; likewise, if consumer rights are violated, the Constitution orders the Ombudsman's Office so that they, through legal actions, try to clean up or repair the violated right in order to make the full one of justice and thus protect the most vulnerable part in this case, the consumers.